Games-Based Learning: An experience report in teaching English during the pandemic - Ortolani, Katherine Nunes Pereira Oliva; Ortolani, Arthur Nogueira (Matraga - Revista do Programa de Pós-Graduação em Letras da UERJ, 2021)
COVID-19 has already taken over millions of lives and has brought the entire world to a halt. It has been a great challenge for teachers and students alike, especially for children. The area of education has reimagined itself. Children began to actively learn through the screens of their computers, tablets, and some, even cellphones. This article brings an experience report about strategies involving the principals and themes of Role-Playing Games used for online classes of English aimed at Brazilian children around the ages of five to nine years old. Role-playing games (at times also spelled as roleplaying games; abbreviated to RPG or RPGs) are games in which the people participating in them (players) assume the roles of characters within a fictional setting. The idea of using RPG strategies to retain the attention of children while teaching from afar, via Zoom, Skype or any other platform that allows the direct interaction between educator and student comes from RPGs’ incredible capacity of transporting the mind of children to a different space, a space of attention and entertainment. As perceived by Tolomei (2017) and also shown in this experience report, motivation and engagement are enhanced through game mechanics. The technique also fulfills the need for human relationships, which has been taken away by COVID-19. ———————————————————————————————————— APRENDIZAGEM BASEADA EM GAMES: UM RELATO DE EXPERIÊNCIA NO ENSINO DE INGLÊS DURANTE A PANDEMIA COVID-19 provocou a morte de milhões de pessoas e fez o mundo inteiro parar. Tem sido um grande desafio para professores e alunos, principalmente para as crianças. A área da educação se reinventou. As crianças começaram a aprender ativamente por meio das telas de seus computadores, tablets e alguns até de seus celulares. Este artigo traz um relato de experiência sobre estratégias envolvendo os princípios e temas dos jogos de RPG usados em aulas online de inglês para crianças brasileiras de cinco a nove anos de idade. Os jogos de RPG são jogos nos quais as pessoas que participam deles assumem o papel de personagens em um cenário fictício. A ideia de usar estratégias de RPG para reter a atenção das crianças durante o ensino à distância, via Zoom, Skype ou qualquer outra plataforma que permita a interação direta entre educador e aluno vem da incrível capacidade dos jogos de RPG de transportar a mente das crianças para um espaço diferente, um espaço de atenção e entretenimento. Conforme percebido por Tolomei (2017) e também demonstrado neste relato de experiência, a motivação e o engajamento são potencializados por meio da mecânica do jogo. As técnicas também atendem à necessidade de relações interpessoais, que foi tirada pelo COVID-19. — Original em inglês.